The Last of the Czars death of a dynasty - Anderson, Mark; Cherfas, Teresa (Bethesda, Md. Discovery Communications, 1996)
The Romanov family ruled Russia for 300 years; an imperial that crumbled in 1918 when Lenin-backed revolutionaries toppled Nicholas II in a violent upheaval. Before their world came crashing down, the Romanovs - Nicholas, Alexandra and their five children - enjoyed a life shrouded in mystery. But with the recent downfall of the Soviet Union, information has come to light, ending generations of speculation. Rare, never-before-seen film footage, actual letter, czarist-era survivor interviews, photos and other rare items give a finely-detailed look at Russian's most dramatic era.
With converted disc.
Executive producer, Phillip Whitehead ; Editors, Christine Pancott ; Series producer, Mark Anderson.
VHS format.
In English.
Keywords: Nicholas -- II -- Emperor of Russia -- 1868-1918.; Nicholas -- II -- Emperor of Russia -- 1868-1918 -- Assassination; Alexandra, Empress, consort of Nicholas II -- Emperor of Russia -- 1872-1918.; Romanov, House of; Russia -- History of Nicholas II, 1894-1917.; Russia -- Kings and rulers -- Biography